Î²- Sitosterol and Betulonic Acid from n-Hexane Extract the Stem Bark of Tetracera indica - Muharni, Muharni; elfita, elfita; Julunar, Julinar; Yohandini, Heni; oktaviani, muthia (Universitas Jenderal Soedirman, 2019)
The Tetraceraindicahasbeen used traditionally to treat various diseases including skin medications, lower blood pressure, fever, headache, wound andgout medicine. The objective of the research was isolatedand characterizedthe ?-sitosterol (1) and betulonicacid (2) fromn-hexaneextract of the stem bark of Tetraceraindica. The dry powder thestembark (550 g)wasmaceration with n-hexane for 24 hrs.Thisextraction process was repeated three times. The n-hexane extract was separated and purified by chromatographytechnique. The structure of isolatedcompound wasdetermined by spectroscopy data UV, IR, NMR and compared with reported data. Two compounds have been isolated and base on spectroscopy data thecompounds is ?-sitosterol (1) andbetulonic acid (2). Betulonic acid is being reported for the first time from T.indica,meanwhile the?-sitosterolpreviously reported from MeOHextractof leaves of T. indicabut is being reported for the first time from the stembarkof T.indica.